An Intervention Ergonomic Framework for Malaysia TVET Higher Education (Global Journals of Research in Engineering, 2024)
Fundamentally an intervention refers to an action that has an agenda and is aimed by the human being to create change Midgley 2020 according to him if the intervention is an action aimed by the human being to create change then systemic intervention is an action aimed at creating a change in the context of reflection to the system The International Association of ergonomics IEA categorizes ergonomics into three specific domains physical organizational and cognitive ergonomics The physical domain is concerned with human anatomy anthropometry physiological and biomechanical characteristics associated with physical activity The domain also consists of working environments and equipment such as hand tools workstations and lighting and ventilation in the workplace The domain of the organization referring to the concern for the optimization of work systems including organizing and even work processes for example as a frequency of work work cycle and rest in addition to directing in performing work The cognitive domain is related to mental processes such as perception memory judgment and motor response Therefore the ergonomic interventions developed should cover all three ergonomic domains namely physical organizational and cognitive Good ergonomic interventions must be carried out prior to the occurrence or reporting of skeletal disorders It is one of the proactive or preventive methods in ensuring the health of a community such as students lecturers and employees at a good level However corrective reactive actions still need to be maintained and taken seriously to curb the symptoms of skeletal disorders
Keywords: intervention; ergonomics; physical; organizational; cognitive